Case Report: Identification of a de novo Microdeletion 1q44 in a Patient With Seizures and Developmental Delay - Tung, Yiehen; Lu, Haiying; Lin, Wenxin; Huang, Tingting; Kim, Samuel; Hu, Guo; Zhang, Gang; Zheng, Guo (Frontiers in Genetics, 2021)
Objective: To explore the correlation between the chromosome microdeletions and phenotype in a child with 1q44 deletion syndrome, we collected the clinical features of the patient and combined them with adjacent copy number variation (CNV) regions previously reported. Methods: We have done a thorough medical history collection on the patient and summarized her clinical symptoms. Whole-exon sequencing (WES) and low-depth whole-genome sequencing (CNV-seq) analysis were performed with DNA extracted from both the patient and her parents’ peripheral blood samples. Chromosome karyotype analysis and fluorescent quantitative PCR (q-PCR) were performed for the use of verification to the CNV regions. Results: A 28.7 KB heterozygosity microdeletion was detected in 1q44 region by whole exon sequencing and low-depth whole genome sequencing. The deleted region included the genes COX20 and HNRNPU2. As verification, karyotype analysis showed no abnormality, and the results of q-PCR were consistent with that of whole-exon sequencing and low-depth whole genome sequencing. Conclusion: The patient was diagnosed with 1q44 microdeletion syndrome with clinical and genetic analysis. Due to the disease appeared in various clinical manifestations and strong genetic heterogeneity, it is difficult to reach the diagnose without genetic examination. Comparing with convention methods, analyzing with both whole-exon sequencing and low-depth whole genome sequencing together has better advantages of high resolution, high throughput, and high sensitivity. With these technics, we can not only improve the diagnostic rate of clinically suspected syndromes that presented with intellectual disability (ID) and multiple malformations but also support further study of the correlation between CNVs and clinical phenotype. This study lays a foundation for the further study of the pathogenesis of complex diseases.